Analysis of the Influence of Loans, Capital Structure, and Company Size on Net Profit in Conventional Commercial Banks Listed on the Indonesia Stock Exchange - Bagas Indrianto Prasetio; Aulia Aulia; Syahrial Hasanuddin Pohan (Universitas Dehasen Bengkulu, 2026)
This study aimed to analyze the effect of customer loans, capital structure, and firm size on net profit in Conventional Commercial Banks listed on the Indonesia Stock Exchange. Customer loans were measured using the loan to assets ratio, capital structure was measured using the debt to equity ratio, firm size was measured using the natural logarithm of total assets, and net profit was measured using the natural logarithm of net profit. The study was conducted in 2025 and employed a quantitative approach with an associative method. The population and sample consisted of 43 banking companies with observation data from 2020 to 2024, resulting in 215 data samples. Secondary data were obtained from the Indonesia Stock Exchange website at idx.co.id. The data were processed using SPSS version 24 software. Data analysis was conducted using multiple linear regression to examine the relationship between the independent variables and the dependent variable. The results showed that customer loans partially had no significant effect on net profit, capital structure partially had a negative and significant effect on net profit, and firm size partially had a positive and significant effect on net profit. Simultaneously, the three independent variables had a positive and significant effect on net profit. Firm size became the most dominant variable influencing net profit, indicated by the highest regression and beta values. The coefficient of determination (adjusted R²) of 0.730 indicated that 73.0% of net profit could be explained by the three independent variables, while the remaining 27.0% was explained by other variables not included in this research model. In addition, the strength of the relationship between the independent variables and the dependent variable was classified as very strong, with a correlation coefficient (R) of 0.857.